2011
DOI: 10.1002/anie.201006057
|View full text |Cite
|
Sign up to set email alerts
|

On the True Photoreactivity Order of {001}, {010}, and {101} Facets of Anatase TiO2 Crystals

Abstract: Design and morphological control of crystal facets is a commonly employed strategy to optimize the performance of various crystalline catalysts from noble metals to semiconductors. [1][2][3][4][5][6][7][8] The basis of this strategy is that surface atomic configuration and coordination, which inherently determine their heterogeneous reactivity, can be finely tuned by morphological control.[3] The conventional understanding of the surface atomic structure of a crystal is that facets with a higher percentage of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

51
1,007
9
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,159 publications
(1,072 citation statements)
references
References 35 publications
51
1,007
9
5
Order By: Relevance
“…It is reasonable to deduce that the accumulation of electrons and holes originates from charge separation on different facets. The origin of the charge separation on the {010} and {110} crystal facets of TiO 2 has been already estimated by theoretical calculation 19 . Similarly, we also evaluated the energy levels of {010} and {110} facets of BiVO 4 by DFT calculation method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reasonable to deduce that the accumulation of electrons and holes originates from charge separation on different facets. The origin of the charge separation on the {010} and {110} crystal facets of TiO 2 has been already estimated by theoretical calculation 19 . Similarly, we also evaluated the energy levels of {010} and {110} facets of BiVO 4 by DFT calculation method.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, certain facets of a semiconductor prefer reduction while others favour oxidation [18][19][20] . However, reports on the reduction and oxidation reaction facets on the same semiconductor crystal (such as TiO 2 ) were often contradictory in the literature [21][22][23][24][25][26] .…”
mentioning
confidence: 99%
“…[5][6][7] However, the required solar-to-fuel efficiencies have been unattainable at a reasonable cost, 8 and there is ample motivation to enhance the photochemical conversion efficiency of the photocatalytic material. A dependency of photocatalytic activity on the surface facet has become evident from a number of experimental studies, [9][10][11][12] though the reasons for this dependency are unknown (see Ref. 13 for proposed mechanisms).…”
Section: Introductionmentioning
confidence: 99%
“…These results show that a slight change occurred along the a and b directions, but there was significant expansion in the c direction, and as a result, the unit cell volume expanded significantly as well [10]. Recent publications showed that the morphology of TiO 2 materials resulted in differences of the enhanced photocatalytic activity for the production of hydrogen between the {101} and {001} facets of anatase tetragonal bipyramidal nanocrystals [11][12][13]. Based on the XRD simulation, Titanium Dioxide -Material for a Sustainable Environmentthe length and width of the peaks were calculated to confirm the percentages of the {101} and {001} facets (Figure 3).…”
Section: General Structure and Properties Of Tiomentioning
confidence: 76%